2015
DOI: 10.1371/journal.pgen.1005579
|View full text |Cite
|
Sign up to set email alerts
|

Inter-population Differences in Retrogene Loss and Expression in Humans

Abstract: Gene retroposition leads to considerable genetic variation between individuals. Recent studies revealed the presence of at least 208 retroduplication variations (RDVs), a class of polymorphisms, in which a retrocopy is present or absent from individual genomes. Most of these RDVs resulted from recent retroduplications. In this study, we used the results of Phase 1 from the 1000 Genomes Project to investigate the variation in loss of ancestral (i.e. shared with other primates) retrocopies among different human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Compared with the research results of Kabza et al [25] on RDVs in humans, which was the only species that has been specifically studied for RDV in the past, some of our research results on RDV in rice were similar to those on human RDV. First, the frequency of most RDVs detected between populations was very low.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Compared with the research results of Kabza et al [25] on RDVs in humans, which was the only species that has been specifically studied for RDV in the past, some of our research results on RDV in rice were similar to those on human RDV. First, the frequency of most RDVs detected between populations was very low.…”
Section: Discussionsupporting
confidence: 75%
“…This supports results from previous studies, showing that many retrogenes have broad expression patterns [56] . Numerous studies have revealed a tendency for retrogenes to be expressed in the human testis [5] , [16] , [25] , which implies a certain connection between the male reproductive organs and retrogenes, and some mechanisms have been confirmed [33] , [57] , [58] . However, the set of analyzed retrogenes is relatively small and may not be fully representative.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Notably, our list does not cover the processed pseudogenes, which represent copies of mRNAs that were copied back into the genome as a side-product of L1-based transposition, 58 , 59 and the human-specific processed pseudogenes are likely to be in the order of hundreds based on the level of detected polymorphic levels. 60 , 61 …”
Section: Discussionmentioning
confidence: 99%